e-Notice Board with improved Security (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Notice boards are widely used to convey messages ranging from small schools to large organizations. This process of conveying messages to the people may lead to wastage of large number of papers in organizations. This will lead to deforestation which causes Global Warming. This study is a small innovative step to enhance this problem by using recent technology. IoT will give solution to this problem by designing a component that which displays the message given by the user. The message that which given by the user will be displayed in the screen. Only an authorized user can access this device to send the voice commands. This remote electronic presentation is utilized to show the information given by the client. The authorized user can speak and the verbalized voice is sent through a Bluetooth and will be displayed on the LCD screen. An android application will be connected with the Bluetooth to receive the voice. A low cost programmed controller named Arduino UNO is used at the receiver to receive and display the messages or information in the LCD display.